2016
DOI: 10.1002/2015jg003186
|View full text |Cite
|
Sign up to set email alerts
|

Net anthropogenic nitrogen inputs (NANI) into the Yangtze River basin and the relationship with riverine nitrogen export

Abstract: This study investigated net anthropogenic nitrogen inputs (NANI, including atmospheric nitrogen deposition, nitrogenous fertilizer use, net nitrogen import in food and feed, and agricultural nitrogen fixation) and the associated relationship with riverine dissolved inorganic nitrogen (DIN) export in the Yangtze River basin during the 1980–2012 period. The total NANI in the Yangtze River basin has increased by more than twofold over the past three decades (3537.0 ± 615.3 to 8176.6 ± 1442.1 kg N km−2 yr−1). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 93 publications
(223 reference statements)
8
82
2
Order By: Relevance
“…Consistent with previous studies that have identified decreased rates of nitrogen fertilizer application as having the potential to reduce nitrogen loading to streams and rivers (Mitsch et al 2001;Chen et al 2016), these findings point to the potential efficacy of decreasing N fertilizer inputs to reduce TN loads and mitigate the negative effects of TN on ecosystem health. However, it is worth noting that TN is not the only variable that influences overall ecosystem health and function, and management and land use change may impact other aspects of ecosystem health such as hydrology (Du et al 2012) and sediment dynamics (Hupp et al 2013), for example.…”
Section: Sensitivity Of Tn Response To Source Reductions and Land Usesupporting
confidence: 87%
“…Consistent with previous studies that have identified decreased rates of nitrogen fertilizer application as having the potential to reduce nitrogen loading to streams and rivers (Mitsch et al 2001;Chen et al 2016), these findings point to the potential efficacy of decreasing N fertilizer inputs to reduce TN loads and mitigate the negative effects of TN on ecosystem health. However, it is worth noting that TN is not the only variable that influences overall ecosystem health and function, and management and land use change may impact other aspects of ecosystem health such as hydrology (Du et al 2012) and sediment dynamics (Hupp et al 2013), for example.…”
Section: Sensitivity Of Tn Response To Source Reductions and Land Usesupporting
confidence: 87%
“…For example, a meta-analysis indicated that on average only 3.6% of net anthropogenic P input would be exported by riverine discharge for 158 watersheds in the world . As a result, more than 90% of annual anthropogenic P input on average do not appear in riverine fluxes but rather must be potentially stored or retained in terrestrial and aquatic landscapes for building up as legacy P pools in many studied watersheds (Chen et al, 2015b(Chen et al, , 2016cGoyette et al, 2016;Han et al, 2012;Russell et al, 2008;Zhang et al, 2015).…”
Section: Excessive Anthropogenic Nutrient Inputsmentioning
confidence: 99%
“…Based on long-term (>30 years) observations, statistical models between annual riverine nitrate flux and previous several years' average net anthropogenic nitrogen inputs (NANI) were developed to address N leaching lag effect in the Mississippi River watershed (previous 2-5 and 6-9 years' average NANI) in 1960-1998(McIsaac et al, 2001) and the Yongan watershed (previous 0-6 years' average NANI) in eastern China in 1980(Chen et al, 2014b. Other several statistical models were directly established between annual riverine nutrient flux and current year's NANI or NAPI, hydroclimatic, and land-use variables in the Yongan watershed and Yangtze watershed in China (Chen et al, 2015b(Chen et al, , 2016c. Using these statistical models, contribution of watershed legacy nutrient sources to riverine nutrient flux was estimated as predicted riverine nutrient fluxes when setting current year's nutrient inputs as zero through adjusting by natural background sources.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…This is especially needed for large rivers like the Yangtze, Pearl and Yellow (see Section 1.5) as their contribution to coastal water pollution might be considerable. A few studies divided the large drainage area into sub-basins for better spatially explicit analyses (Bao et al 2006;Chen et al 2016;Liu et al 2008a). But these studies are mainly for the Yangtze and focus more on nutrient budgets of agricultural Sections 1.2.2 and 1.2.3).…”
Section: Causes Of Nutrient Pollution In Riversmentioning
confidence: 99%
“…Chapter 7 * Except for NUFER, a few other models exist to quantify nutrient balances for agricultural systems in all of China (e.g., Chen et al 2016;Chen et al 2008a). NUFER was chosen here for the comparison because it quantifies nutrient flows in the food chain that consists of not only agricultural systems (crop and animal), but also food processing and household systems.…”
Section: Nutrient Models For Chinamentioning
confidence: 99%